CONTEMPORARY CHALLENGES IN TFCC MANAGEMENT: A MULTIFACTORIAL CLINICAL ANALYSIS OF CURRENT EVIDENCE - Szurna, Katarzyna; Suprun, Tomasz; Rytel, Jan; Modzelewska, Anna Maria; Walczewski, Jakub; Kondrat, Ada; Majewski, Wojciech Franciszek; Twarowska, Zuzanna; Stawowski, Sylwester; Rusiłowicz, Urszula; Bolesta- Okuniewska, Emilia; Pietrasz, Michał (International Journal of Innovative Technologies in Social Science, 2026)
Background: The triangular fibrocartilage complex (TFCC) is a crucial stabilizer of the wrist, traditionally associated with sports- related trauma. However, increasing evidence suggests a wider etiological spectrum. Aim: This literature review aims to synthesize current evidence (2015- 2025) regarding the risk factors, mechanisms of injury, and management of TFCC lesions, emphasizing its prevalence beyond athletic populations. Material and methods: A systematic search was conducted across PubMed, Web of Science, and Wiley Online Library using the keywords: "triangular fibrocartilage complex," "TFCC," "arthroscopy," and "wrist injuries." The selection included RCTs, prospective and retrospective cohort studies, and case series published in English between 2015 and 2025. Case reports were strictly excluded. A total of 37 articles met the criteria for final synthesis. Results: While acute traumatic tears (Palmer Type I) remain prevalent in overhead and axial-loading sports, anatomical predispositions- specifically positive ulnar variance- and age- related degenerative changes (Palmer Type II) are significant risk factors in non-athletic populations. Modern diagnostics have evolved with MR arthrography showing superior sensitivity over conventional MRI, although diagnostic arthroscopy remains the gold standard. Management has shifted toward minimally invasive arthroscopic techniques, particularly foveal reattachment using suture anchors and modified suturing methods, which demonstrate favorable long-term outcomes and improved quality of life. Conclusions: TFCC pathology is a multifaceted condition that should not be viewed solely as a sports injury. Understanding the interplay between anatomical, occupational, and traumatic factors is essential for accurate diagnosis and effective patient-centered management. Clinicians must adopt a broad etiological perspective to prevent chronic disability and optimize functional recovery.